Evaluation of the antinociceptive and anti-inflammatory effects of the acetone extract from Anacardium occidentale L - Frederico Argollo Vanderlinde; Higor Frutuoso Landim; Elson Alves Costa; Pablinny Moreira Galdino; Maria Aparecida Medeiros Maciel; Gineide Conceição dos Anjos; David do Carmo Malvar; Wellington da Silva Côrtes; Fábio Fagundes da Rocha (Universidade de São Paulo, 2009)
The stem bark of Anacardium occidentale L. (Anacardiaceae), commonly called cashew, is used in Brazilian traditional medicine for the treatment of gastric and inflammatory disorders. The present study was carried out to investigate the in vivo anti-inflammatory activities of the acetone extract (AE) of the stem bark of A. occidentale. We evaluated the pharmacological activities of this plant material through the analgesic, antiedematogenic and chemotaxic inhibitory effects produced by the AE. The oral administration (p.o.) of mice with the AE (0.1, 0.3 and 1.0 g/kg) or positive control indomethacin (10 mg/kg) inhibited acetic acid-induced writhing by 18.9, 35.9, 62.9 and 68.9%, respectively (ID50% = 530 mg/kg). The highest dose of the AE was able to inhibit croton oil-induced ear edema formation by 56.8% (indomethacin at 10 mg/kg, p.o. - 57.6% inhibition). When submitted to the carrageenan-induced peritonitis test, the AE (0.1, 0.3 and 1.0 g/kg, p.o.) impaired leukocyte migration into the peritoneal cavity by 24.8, 40.5 and 49.6%, respectively. The positive control, dexamethasone (2 mg/kg, s.c.), inhibited leukocyte migration by 66.9%. These results indicate the presence of anti-inflammatory and antinociceptive principles in the acetone extract of Anacardium occidentale, and reinforce the plant's potential therapeutic use against pain and inflammatory diseases. As cascas do caule do Anacardium occidentale L. (Anacardiaceae), conhecido como cajueiro, são popularmente utilizadas no Brasil para o tratamento de doenças gástricas e inflamatórias. Este estudo teve como objetivo a avaliação farmacológica in vivo da atividade antiinflamatória do extrato acetônico (AE) obtido das cascas do A. occidentale, investigando os efeitos analgésico, antiedematogênico e inibitório sobre a quimiotaxia deste material botânico. A administração oral (p.o.) em camundongos com o AE (0,1; 0,3 e 1 g/kg) ou o controle positivo indometacina (10 mg/kg) inibiu as contorções abdominais induzidas pelo ácido acético em 18,9; 35,9; 62,9 e 68,9% respectivamente (ID50% = 530 mg/kg). Esta maior dose do AE também inibiu o edema de orelha produzido pelo óleo de cróton em 56,8% (indometacina, 10 mg/kg, p.o. - 57,6% de inibição). No teste da peritonite induzido pela carragenina, o AE (0,1; 0,3; e 1,0 mg/kg, p.o.) reduziu a migração de leucócitos para a cavidade peritoneal em 24,8; 40,5; e 49,6% respectivamente, enquanto que o controle positivo dexametasona (2 mg/kg, s.c.) inibiu a migração de leucócitos em 66,9%. Estes resultados indicam a presença de princípios ativos antiinflamatórios e antinociceptivos no extrato acetônico de Anacardium occidentale e reforçam o potencial terapêutico da planta em doenças que envolvem dor e inflamação.